2008
DOI: 10.1007/s10570-008-9197-5
|View full text |Cite
|
Sign up to set email alerts
|

Tosylation and acylation of cellulose in 1-allyl-3-methylimidazolium chloride

Abstract: Tosylation and acylation of cellulose were performed under mild reaction conditions using imidazolium based ionic liquids (ILs) as solvents. The non-degradative nature, lower viscosity, as well as higher solubility of cellulose in [amim]Cl encouraged us to carry out the reactions in this media. The reactions described here were optimised for this particular solvent in order to obtain different cellulose derivatives with high yields, homogeneity and degree of substitution (DS). Two reagents employed for the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 32 publications
0
69
0
3
Order By: Relevance
“…Homogeneous reaction yielding tosylated cellulose can be carried out in [Amim]Cl, and aspects such as the degree of tosylation, the reaction temperature and the base can be varied, e.g., trimethylamine is not fully mixed with [Amim]Cl, however, pyridine works efficiently [172]. The homogeneous reaction produces a predominant conversion of primary hydroxyl groups at DS values up to 1 [173,174].…”
Section: Esterificationmentioning
confidence: 99%
“…Homogeneous reaction yielding tosylated cellulose can be carried out in [Amim]Cl, and aspects such as the degree of tosylation, the reaction temperature and the base can be varied, e.g., trimethylamine is not fully mixed with [Amim]Cl, however, pyridine works efficiently [172]. The homogeneous reaction produces a predominant conversion of primary hydroxyl groups at DS values up to 1 [173,174].…”
Section: Esterificationmentioning
confidence: 99%
“…Several methods have been developed to prepare LCCEs. These methods involved heterogeneous acylation by using acyl chloride, acid chlorides under vacuum or aliphatic acids with trifluoroacetic acid [3], and homogeneous acylation in DMAc/LiCl [4][5][6] or in ionic liquids [7,8]. Studies have shown that the maximum degree of substitution (DS) of LCCEs synthesized in ionic liquid system was up to approximately 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…Acylation of cellulose with linear chain acylation reagents such as anhydride or chloride is the most common method to produce cellulosic bioproducts. Because of the wide application of cellulose acetate, cellulose acetylation with acetic anhydride or acetyl chloride in ILs has been extensively studied, and cellulose acetates with high degree of substitution (DS) were easily prepared (Wu et al, 2004;Abbott et al, 2005;Heinze et al, 2005;Barthel & Heinze, 2006;Granstrom et al, 2008). Furthermore, ILs were also be reported as reaction media for cellulose modification with other liquid reagents, such as carbanilation with phenyl isocyanate (Barthel & Heinze, 2006;Schlufter et al, 2006), acylation with lauroyl chloride (Barthel & Heinze, 2006), and perpropionylation with propionic anhydride (Schlufter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%